Analisis Perlindungan Data Pribadi bagi Pengguna E-commerce Menurut Perspektif Hukum di Indonesia - Nabila, Laela; Setianingrum, Reni Budi (Media of Law and Sharia, 2024)
The development of technology in Indonesia means that buying and selling transactions can also be done electronically without having to meet face-to-face between sellers and buyers, namely through electronic commerce platforms or e-commerce. Through this e-commerce platform, a buyer must include personal data such as name, residential address and mobile phone number. The purpose of this research is to find out how the regulations regarding the protection of personal data for e-commerce users in Indonesia and what sanctions are given to e-commerce companies as electronic system providers if there is a leak of user personal data. The research method used by the author is the normative juridical method and statute approach. From the research results obtained, the protection of personal data in Indonesia is regulated in Law Number 27 of 2022 and ITE Law. The conclusion is that the protection of personal data in Indonesia already has regulations that regulate so there is no need to worry if you are going to make buying and selling transactions through e-commerce